Antibiotic resistance pattern of bacteria isolated from various clinical specimens in a tertiary care hospital - B. S. G Sailaja; P.D. Prasad (Tropical Journal of Pathology and Microbiology, 2019)
Background: Antibiotic resistance is a common phenomenon in bacteria, and it is a significant threat all over the world. With this a study was conducted to find the antibiotic resistance pattern of various bacterial isolates.Methods: This is a hospital-based study involving both in and outpatients. Patients with various infections were included, clinical specimen were collected accordingly. The pathogenic bacteria were isolated and identified. Antibiotic sensitivity testing was done by Kirby Bauer disc diffusion method.Results: The male female ratio was 1.23; 30% isolates were gram positive cocci and 70% were gram negative bacilli; Klebsiella spp (30.5%) was the predominant isolate followed by Staphylococcus aureus (25%); statistically the difference was not significant. Samples wise, predominant isolates were from urine followed by respiratory samples and skin samples; significant drug resistance was detected.Conclusion: A Significant rise of antibiotic resistance to various antibiotics in different classes of bacteria has been observed. Always there should be proper communication between the clinician and microbiologists is essential to get the best result while treating patient.